Web-Based Motor Intervention to Increase Health-Related Physical Fitness in Children With Congenital Heart Disease: A Study Protocol - Meyer, Michael; Hreinsdottir, Adalheidur; Häcker, Anna-Luisa; Brudy, Leon; Oberhoffer, Renate; Ewert, Peter; Müller, Jan (Frontiers in Pediatrics, 2018)
Objective: Exercise interventions are underutilized in children with congenital heart disease (CHD) especially when the primary outcome is not peak oxygen uptake. Most of the studies are restricted to a low sample size and proximity of the patients to the study centers. Now eHealth approaches bear a promising but also challenging opportunity to transmit such intervention programs to participants, and check progress and compliance from remote. This study aims to improve health-related physical fitness (HRPF) with a 24 weeks web-based exercise intervention. Methods and design: The current study is a randomized control trial (RCT) with a crossover design and the aim to improve functional outcome measures. It also estimates adherence and feasibility in patients with CHD in this web-based exercise/motor intervention over 24 weeks. Primary outcome is the improvement of HRPF. Secondary outcomes are, functional and structural arterial stiffness measures and health-related quality of life. Thus, 70 children from 10 to 18 years with CHD of moderate and complex severity will be recruited and allocated randomly 1:1 in two study arms after baseline testing for their HRPF, arterial stiffness measures and health-related quality of life. For 24 weeks, participants in the intervention arm receive three weekly exercise video clips of 20 minutes each. Every video clip comprises 20 child-oriented exercises which have to be executed for 30 seconds followed by a recovery period of 30 seconds. Each session starts with 3 to 4 warming-up exercises, followed by 10 to 12 strength and flexibility exercises, and ending with 3 to 4 minutes of cool down or stretching tasks. Continuous video clips are streamed from a web-based e-Learning platform. The participant simply has to imitate the execution and follow some short advices. After each session, a brief online survey will be conducted to assess perceived exertion and feasibility. Discussion: The study will help to determine the efficacy and applicability of a web-based exercise intervention in children with CHD in regard to functional outcome measures. In addition, it will outline the effectiveness of remote monitoring, which provides a cost effective approach to reach patients with CHD that are low in prevalence and often